(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الدراسة إلى معرفة مدى تقييم معلمي التعليم الأساسي في محافظة اللاذقية للتعليم المستمر الذي تنتهجه وزارة التربية للنهوض بالمستوى المهني و الشخصي للمعلم ، و الذي تم اختصاره في الدورات التدريبية على المناهج الجديدة ، من خلال أربع محاور للتقييم هي ( تخطيط الدورات التدريبية ، محتوى الدورات التدريبية تنفيذ الدورات التدريبية ، المستوى المهني و الشخصي للمعلم ) . و معرفة الفروق بين متوسط إجابات أفراد العينة في هذه المحاور . استخدمنا في هذا البحث المنهج الوصفي التحليلي، و اعتمدنا على الاستبانة لمعرفة آراء المبحوثين ، من خلال سحب عينة عشوائية تضمنت 385 معلم و معلمة من مرحلة التعليم الأساسي في محافظة اللاذقية . ثم تفريغ الاستجابات بواسطة البرنامج الاحصائي SPSS.23 ، و تحليل البيانات ، و استخلاص النتائج التي كان من أهمها ما يلي : - الدورات التدريبية لم تحقق الأهداف المرجوة منها في تطوير المستوى المهني و الشخصي للمعلم ، بسبب ضعف التخطيط لهذه الدورات ، و المحتوى التقليدي ، و عدم تنفيذها بالطريقة المخططة . حيث جاءت درجة تقييم المعلمين ضمن عينة البحث لجميع هذه المحاور ضمن المجال القليل . The objective of this study was to assess the assessment of the teachers of basic education in Lattakia To lifelong learning , adopted by the Ministry of education to improve the professional and personal level of the teacher , which was shortened in training courses on new curricula , through four of assessment ( planning of training courses- courses content – implementation of training courses – the professional and personal level of the teacher) to find the differences between the average responses of the sample members in these axes . - In this research we used the analytical descriptive method , and we relied on the questionnaire to know the views of the respondents , through the withdrawal of teachers from the basic education in Lattakia , and then unloading the responses by statistical program SPSS.23 , and analyze the data , and extract the results . whichever is the most important : - Training courses didn’t achieve the desired goals in the development of theprofessional and personal level of the teacher , due to poor planning of these courses , and traditional content , and don’t implemented in the planned manner , where the degree of evaluation of teachers within the sample of all these topics in the level of little .